E-Islamic Law: Solusi Kulturisasi Hukum Islam sebagai Langkah Menormatifkan Tujuan Hukum Islam Menjadi Hukum Positif - Winda Sari; Desi Fitriyani (CV Rewang Rencang, 2021)
This research presents Islamic law's objectives that are chosen as the solution to be adopted. So, it should be contained as the positive law norm in Indonesia. In this research, the researchers used normative legal research methods and literature study, through a conceptual approach. Unfortunately, the societies' culture regarding the objectives of Islamic law is still weak and being problematic. Therefore, the researchers present the E-Islamic Law application as a culturalization medium to solve it. E-Islamic Law acts as a bridge, so the content of legal objectives will be a positive legal norm in Indonesia.